2009
DOI: 10.1002/ejsp.615
|View full text |Cite
|
Sign up to set email alerts
|

Who is watching over you? The role of shared identity in perceptions of surveillance

Abstract: Two studies were conducted to investigate the role of social identity in appraisals of the purpose and acceptance of surveillance. In Study 1 (N ¼ 112), a survey study demonstrated that there is a negative relationship between identification with one's city and the extent to which public closed circuit television (CCTV) surveillance is perceived as an invasion of privacy. This relationship was mediated by perceptions that the purpose of surveillance is to ensure safety. Study 2 (N ¼ 139) manipulated identity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For instance, studies of attitudes towards CCTV generally indicate support for it [12], but this changes when social relationship with the source of the surveillance changes [22]. Our subjects knew who the surveillors were and (partially) their intentions, which makes the situation different from most public surveillance situations, as predicted by trust-formation models [11,30] and social identity theory [22]. Moreover, as our data on unwillingness to disclose data suggest, "keeping face" with one's social network, or the public, instead of researchers would open entirely new privacy issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies of attitudes towards CCTV generally indicate support for it [12], but this changes when social relationship with the source of the surveillance changes [22]. Our subjects knew who the surveillors were and (partially) their intentions, which makes the situation different from most public surveillance situations, as predicted by trust-formation models [11,30] and social identity theory [22]. Moreover, as our data on unwillingness to disclose data suggest, "keeping face" with one's social network, or the public, instead of researchers would open entirely new privacy issues.…”
Section: Discussionmentioning
confidence: 99%
“…Social identity theory suggests that perceptions of privacy intrusion depend on the relationship with the source of surveillance: Surveillance is more acceptable when originating from a group with which one identifies or shares an identity [22]. Given that the subjects met most of the researchers on the project team, and that the team members are about as young as the subjects, the surveillance they execute may be perceived more favorably.…”
Section: Background: Understanding Privacymentioning
confidence: 99%
“…This data can then be extensively profiled and distributed amongst third parties who are often authorised to receive this data through permission given by checking (or failing to uncheck) the tick box on a term and conditions form or hidden -in plain sight -within the text of privacy policies. However, in a recent study, O'Donnell et al (2010a) argue that surveillance should not be judged directly as either good or bad as its perception is influenced by additional factors. They (O'Donnell et al 2010a) focus upon the way in which perceptions of surveillance are affected by contextual influences directly relating to the form and location of the surveillance.…”
Section: Privacy In a Technologically Saturated Worldmentioning
confidence: 99%
“…It has been shown that socio-demographic variables influence several security technology related factors: For example, men are more interested in systems than women (Samson & Huber, 2010). Studies exploring reactions to CCTV show that the infringement of privacy was rated higher by men than by women (Spriggs et al, 2005) and higher by younger than by older people (O'Donnell, Jetten, & Ryan, 2010;Spriggs et al, 2005). Females regard the incident of a risky event more probable than men (Lerner et al, 2003).…”
Section: Potential Predictors Of the Attitude Towards The Use Of Bodymentioning
confidence: 99%